Fenomena Multi Peran Wanita Karir pada Masa Pandemi Covid-19 di Kecamatan Tegalombo Kabupaten Pacitan - Suci Restiati; Khusniati Rofiah (Institut Agama Islam Negeri Ponorogo, 2022)
Career women do not mean having to work in an office, but they can also work from home, for example, selling online. It is intended that when women encounter a problem, they already have the provision of strong soft skills and hard skills so that they can help in dealing with the rigours of life. Therefore, it is hoped that this district will be able to excel in accordance with the expectations of the demands and needs of the times. So this study aims to describe the standard of multi-role career women, their programs, and their planning in the Tegalombo District. The research method used is qualitative with the type of phenomenological study and data collection methods using interviews, observation, and documentation. This research results in the position of career women's roles in economic prosperity, family education, and household harmony. It is hoped that the multi-role of career women in the Covid-19 era can describe the problems that occur, and further direct the quality and quantity of career women in improving survival.